Desjudicialização por meio das serventias extrajudiciais e acesso à justiça : análise acerca da (im)possibilidade de tornar obrigatória a via administrativa - Dadalto, Rafael Gaburro (2019)
The process proved incapable of ensuring effectiveness of the demands of today's complex and dynamic society, revealing the so-called "crisis of the process" and consequently of access to the just legal order. Faced with this, it is inevitable that procedures are dejudicialization. But the question is whether the model of dejudicialization proposed by the new Brazilian minisystem of consensual methods of conflict resolution should pass or should go through extrajudicial services and, if once removed from the judiciary certain procedure, there would be an obligation to use the administrative sphere (less in some cases), there is sight the principle of inafasability of the jurisdiction. As for the first questioning, it does not show any doubts, based on the analysis of numerous examples coming from the most diverse legislation, such as the insertion of the norms in article 175 of the new CPC and in article 42 of the Mediation Law. However, in relation to the second, even if one considers the reinterpretation of access to justice and the unfatability of the jurisdiction, as well as the evolution of the notarial function, this is not a quiet situation in the doctrine and jurisprudence. To achieve the appropriate premise, the technique of bibliographical and documentary research and the comparative method are used in order to establish the doctrinal divergences, positioning itself on the topic hereafter.